Pengaruh Self Disclosure dan Self Efficacy Terhadap Tingkat Setres pada Mahasiswa - Fadhilah, Nurul; Sari, Dewi Nur Puspita; Winarni, Lastri Mei (Universitas Hamzanwadi, 2022)
Thesis task is a final task that is difficult and takes a long time so that students feel burdened with their assignments which will have an impact on stress. The cause of stress in students can be due to internal or external problems. 67.4% of nursing students who are working on their thesis experience mild stress. Students who have low self-disclosure and self-efficacy will experience high stress, so that it can affect students in doing thesis. This study aims to determine the effect of self-disclosure and self-efficacy on stress levels in students who are working on a thesis. The design of this study was quantitative with a cross sectional approach. This research was conducted at Yatsi Madani University in June 2022. The population in this study were regular final year students at Yatsi Madani University. The sampling technique used total sampling with a total of 227 students as respondents. The instruments in this study used the Jung's Type Indicator (JTI) questionnaire, self disclosure scale, self efficacy scale and stress scale for. Bivariate analysis in this study used the Chi-Square test. Of the 227 students, the majority aged 21-23, 97.8%, female 87.2%, having an extrovert personality as much as 96.9%, self-disclosure and self-efficacy in dominant students in the moderate category as many as 86.8 % and 73.6%, and the majority fall into low stress levels as much as 67.4%. The results of the Chi-Square test obtained a p-value of 0.001 <0.05, which means that there is an influence between self-disclosure and self-efficacy on stress levels in students. This study can be used as a reference to get an overview of the three variables so that they can provide nursing interventions to students.